DIGITAL SKILL DURING COVID-19: EFFECTS OF DIGITAL LEADERSHIP AND DIGITAL COLLABORATION - Saputra, Nopriadi; Nugroho, Riant; Aisyah, Hesty; Karneli, Okta (Jurnal Aplikasi Manajemen, 2021)
The inequality of digital skills is an organizational challenge experienced by public and private organizations to ensure work productivity in work-from-home arrangements during Covid-19. This article aims to elaborate on digital skill development and examine the effects of digital leadership and digital collaboration on digital skill development. This article is based on a cross-sectional study involved 824 office workers from 32 provinces in Indonesia. The combined convenience and snowballing approach were used as the sampling methods. The collected data were structured in the first-order constructs by PLS Structural Equation Modeling. The results revealed that digital skills are significantly influenced directly by digital collaboration and indirectly by digital leadership. For accelerating digital skill development, the superior of office workers should facilitate their team members to collaborate intensively by using digital technology. Further study is recommended to examine the effects of other factors such as work motivation, family support, and availability of digital facility at home, performance management, and perceived organizational support.